On t-Neighbourhoods in Trigonometric Topological Spaces - et. al., S. Malathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we introduce a new type of neighbourhoods, namely, t-neighbourhoods in trigonometric topological spaces and study their basic properties. Also, we discuss the relationship between neighbourhoods and t-neighbourhoods. Further, we give the necessary condition for t-neighbourhoods in trigonometric topological spaces. .